Combined treatment of non‐small cell lung cancer using radiotherapy and immunotherapy: challenges and updates. Issue 11 (17th October 2021) - Shang, Shijie; Liu, Jie; Verma, Vivek; Wu, Meng; Welsh, James; Yu, Jinming; Chen, Dawei
Abstract: The efficacy of immunotherapy for advanced non‐small cell lung cancer (NSCLC) remains unsatisfactory, as the majority of patients either do not experience an objective response or acquire secondary resistance. As a result, several methods to enhance the systemic efficacy of immunotherapy have been investigated, including a large area of active research by combining immunotherapy with radiation therapy (RT). Given the rapidly burgeoning concept of combining immunotherapy and RT for increasing therapeutic benefit, we review the progress in this field thus far and explore further avenues for enhancing this combination. This review commences with a discussion of the only two existing randomized trials (and a pooled analysis) showing that the addition of RT to immunotherapy improves the abscopal response rate, progression‐free survival, and overall survival in metastatic NSCLC patients. We then discussed factors and biomarkers that may be associated with a proportionally greater benefit to additional RT, such as low programmed cell death protein ligand 1 (PD‐L1) status, tumor mutational burden (TMB), and patient's immune function. Next, the implementation of RT to overcome immunotherapy resistance is discussed, including a mechanistic discussion and methods with which these mechanisms could be exploited. Lastly, the emerging role of low‐dose RT is discussed, which may help to overcome inhibitory signals in the tumor stroma that limit T‐cell infiltration. Taken together, given the current state of this rapidly expanding realm, these futuristic strategies may be reflected upon to further enhance the efficacy of immunotherapy for a wider group of patients. Abstract : In recent years, immunotherapy has been considered the most promising method to overcome cancer and extend survival. It has been widely reported in preclinical and clinical studies that radiotherapy induces immunomodulatory effects by releasing TAAs and activating immunoregulation‐related signaling pathways, initiating tumor‐specific cytotoxic T cells, and promoting T cells to enter into tumor tissues. In this manuscript, we summarize the current status of immunotherapy and iRT and the development and additional combination strategies to enhance the efficacy of iRT.